THE ROLE OF THE MARKETING MIX IN ACHIEVING CUSTOMER LOYALTY-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT THE KALEH FACTORY FOR DAIRY PRODUCTS IN THE HOLY CITY OF KARBALA - Nagham Dayekh Abd Ali (Scholars Digest Publishing, 2025)
The current research was concerned with studying the nature of the relationship and the influence between two variables represented by (marketing mix and customer loyalty ) . The research sample was a group of workers in the Kaleh Dairy Factory in the holy city of Karbala. The data collection department distributed the questionnaire to obtain the sample’s opinions about the research variables and to reach accurate answers about the nature of the factory’s adoption of the research variables. and the nature of the answers was analyzed statistically through the spss statistical program to get to the fact of accepting or rejecting the two hypotheses of the research, which are the hypotheses of correlation and influence relationships, and through the statistical results, the two hypothesis was accepted based on the level Statistical significance. The research reached a set of recommendations that support the application of the concept of marketing mix in the factory, which means Markets consider the elements of the marketing mix as an important and influential factor for success, achieving a competitive advantage, and enhancing customer loyalty.
Keywords: Marketing mix, customer loyalty, dairy products, promotion strategy, pricing